THE EFFECT OF USING VIDEO ON STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT - Liliana Dewinta Br. Tarigan; Rahmad Husein (Universitas Negeri Medan, 2016)
This research deals with the effect of using video on students’ achievement in writing descriptive text. The population of this research was the students of VIII SMP of SMP Negeri 4 Stabat in Academic Year 2016 / 2017. This research was conducted with two randomized groups namely experimental group and control group. The experimental group was taught by using video and the control group was taught without using video. The researcher collected the data by giving essay test in the written test form. In order to know the reliability of the test, the researcher used inter-rater formula. The result of the reliability was 0.73. The data was analyzed by using t-test formula. The analysis showed that the mean scores of the students in the experimental group was significantly higher than the mean scores of the students in the control group at the level of significant α= 0.05 with the degree of freedom (df) 58 with tobserved value 8.871 > ttable value 2.000. Therefore, null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. The finding indicated that video significantly affected the students’ achievement in writing descriptive text.